PENYAJIAN AKTIVA TETAP PADA LAPORAN KEUANGAN PT. YAMAHA SERBA MULIA AUTO CABANG LOA JANAN - Imam Nazarudin Latif, Asmawati, Elfreda Aplonia Lau, (EKONOMIA, 2015)
This study aims to determine whether the measurement, presentation and reporting of fixed assets PT. Yamaha Serba Mulia Auto Loa Branch Janan was appropriate or not is accordance with SFAS No.17.Basic theory used : the effect on the financial accounting, measurement, presentation and reporting of fixed assets. Hipotesis research aims the measurement, presentation and reporting of fixed assets PT. Yamaha Serba Muia Auto Loa Branch Janan not in accordance with SFASNo. 17.Data collection is done by using field research and liberary. Data used in the financial statement PT. Yamaha Serba Mulia Auto Loa Branch Janan. consisting of balance sheet, incame statement and list of fixed assets during the fourth financial year (period 2010-2013).The analysis tool is the depreciation using the staright-line method followed by measurement, presentation and reporting of fixed assets.Based on the analysis and discussion that has been conducted acquired company’s incame statement at the end of 2013 a profit of Rp. 986.951.442,00, after correction and recalculation based financial accounting standards obtained at the company’s incame statement for the year 2013 by Rp. 1.076.378.281,00 of the calculation there is a difference of Rp. 89.428.839,00. Wheareas according to the company’s depreciation costs Rp. 92.272.479,33 and depreciation charges under SFAS No. 17 Rp. 122.082.092,33 means the difference in cost of Rp. 29.809.613,00. Thus after adjusting statement of financial accounting standards no. 17, then the need for a journal adjusment required as a correction in the valuation remains fixed assets 2013  so natural to at present.